An epigenetic switch activates bacterial quorum sensing and horizontal transfer of an integrative and conjugative element - Ramsay, Josh; Bastholm, T.R.; Verdonk, Callum J.; Tambalo, D.D.; Sullivan, J.T.; Harold, L.K.; Panganiban, Beatrice A.; Colombi, Elena; Perry, B.J.; Jowsey, W.; Morris, C.; Hynes, M.F.; et al. (OXFORD UNIV PRESS, 2022)
Horizontal transfer of the integrative and conjugative element ICEMlSymR7A converts non-symbiotic Mesorhizobium spp. into nitrogen-fixing legume symbionts. Here, we discover subpopulations of Mesorhizobium japonicum R7A become epigenetically primed for quorum-sensing (QS) and QS-activated horizontal transfer. Isolated populations in this state termed R7A* maintained these phenotypes in laboratory culture but did not transfer the R7A* state to recipients of ICEMlSymR7A following conjugation. We previously demonstrated ICEMlSymR7A transfer and QS are repressed by the antiactivator QseM in R7A populations and that the adjacently-coded DNA-binding protein QseC represses qseM transcription. Here RNA-sequencing revealed qseM expression was repressed in R7A* cells and that RNA antisense to qseC was abundant in R7A but not R7A*. Deletion of the antisense-qseC promoter converted cells into an R7A*-like state. An adjacently coded QseC2 protein bound two operator sites and repressed antisense-qseC transcription. Plasmid overexpression of QseC2 stimulated the R7A* state, which persisted following curing of this plasmid. The epigenetic maintenance of the R7A* state required ICEMlSymR7A-encoded copies of both qseC and qseC2. Therefore, QseC and QseC2, together with their DNA-binding sites and overlapping promoters, form a stable epigenetic switch that establishes binary control over qseM transcription and primes a subpopulation of R7A cells for QS and horizontal transfer.